Postoperative treatment with octreotide in patients with gastroesophageal cancer: An open-label phase 2 study - Anders Holmén; Maria Lampi; Ioannis Rouvelas; Berit Sunde; Thorhallur Agustsson; Greger Lindberg; Fredrik Klevebro (Clinical Nutrition Open Science)
Summary: Background & Aims: Dietary peptides are hypothesized to contribute to persistent weight loss following gastrectomy or esophagectomy in cancer patients. Previous studies have suggested that this effect might be partially mitigated by Octreotide. This study aimed to evaluate the safety and tolerability of intramuscular Sandostatin® (Octreotide Long-Acting Release [LAR] depot 10mg) focusing on the incidence and characterization of adverse events. Methods: A prospective open-label phase-2 study was conducted from September 2021 to October 2023. Twenty patients (10 undergoing gastrectomy and 10 undergoing esophagectomy) were enrolled. Each patient received three doses of intramuscular Sandostatin® LAR depot 10mg at 7 days, 1 month, and 2 months post-surgery. All patients were evaluated at 7 days and at 1-, 2-, 3-, and 6-months post-surgery.The primary endpoint was safety, assessed by the incidence and characterization of adverse events, with no occurrence of serious adverse events defined as successful. Tolerability was defined as at the completion of the treatment protocol by at least 90% of patients.Secondary endpoints included weight loss (percentage from baseline), Health-Related Quality of Life (assessed by the European Organisation for Research and Treatment of Cancer Core Quality of life Questionnaire [EORTC-QLQ-C30] and Quality of life Questionnaire for Oesophago-Gastric symptoms [EORTC-QLQ-OG25]) at baseline and at 1-, 2-, 3-, and 6-months post-surgery, and the proportion of patients requiring enteral nutrition via jejunostomy. Results: The study was completed by 95% of participants. Serious adverse events were observed but were not attributed to the Octreotide treatment. Median weight loss at 6 months was 11% (3 months: 7%, 2 months: 4%, 1 month: 5%). Mean Global Quality of Life, as assessed by the of EORTC-QLQ-C30, declined at 1 month after surgery but promptly recovered to align with the baseline level (67.6 at baseline vs. 67.2 at 6 months). Among patients undergone esophagectomy, the percentage of patients requiring enteral nutrition was 80%, 60%, and 30% at 1-, 2-, and 3-months, respectively. Conclusions: This study demonstrates that Octreotide treatment was well tolerated and safe, with no serious adverse events attributed to the Octreotide treatment. Observed weight loss, Health-Related Quality of Life, and the proportion of patients requiring enteral nutrition aligned with expectations. Future studies should consider a double-blinded randomized controlled design preferably with a dose-response assessment to enable a more robust investigation.